Death in Times of SARS-CoV-2 Pandemic. Legal Regulations of the Burial of the COVID-19 Deceased in Poland - Szczot, Elżbieta (Review of European and Comparative Law, 2021)
The article discusses the issues of death in times of the SARS-CoV-2 pandemic and burial of the COVID-19 deceased. It also presents some currently binding legal regulations as well as restrictions and obligations for the organizers of the funeral connected with the infection of the deceased with COVID-19. Moreover, it shows the influence of state law on funeral regulations in the denominational form and the cult of memory of the dead.